2024
DOI: 10.1002/adfm.202402307
|View full text |Cite
|
Sign up to set email alerts
|

Burgeoning Silicon/MXene Nanocomposites for Lithium Ion Batteries: A Review

Peng Zhang,
Xindi Wang,
Yifan Zhang
et al.

Abstract: Silicon‐based materials are regarded as the most promising negative electrode materials for next‐generation high‐energy lithium ion batteries due to their high theoretical capacity, low lithiation plateau and low cost, but they still suffer from dramatic volume variation during charge/discharge and sluggish kinetics, substantially restricting their practical applications. Recently, 2D MXenes are demonstrated to improve the electrochemical performances of Si‐based materials owing to their metallic conductivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 118 publications
0
0
0
Order By: Relevance
“…36–38 They have shown potential in the most representative energy storage systems, such as supercapacitors and secondary batteries. 39–44 Supercapacitors have high power density and fast charging and discharging rates, making them suitable for mobile applications such as power sources for electric vehicles. 45,46 The demand for carbon emission suppression has driven current interest in hybrid vehicles, occupying an increasing market share and greatly stimulating research interest in low-cost and long cycle-life batteries.…”
Section: Mxenes In Electrochemical Energy Storagementioning
confidence: 99%
“…36–38 They have shown potential in the most representative energy storage systems, such as supercapacitors and secondary batteries. 39–44 Supercapacitors have high power density and fast charging and discharging rates, making them suitable for mobile applications such as power sources for electric vehicles. 45,46 The demand for carbon emission suppression has driven current interest in hybrid vehicles, occupying an increasing market share and greatly stimulating research interest in low-cost and long cycle-life batteries.…”
Section: Mxenes In Electrochemical Energy Storagementioning
confidence: 99%
“…19,20 Moreover, the abundant end groups (e.g., -OH, -F) on the Ti 3 C 2 T x nanolayers are more conducive to forming interfacial assemblies with other substances. 21,22 Recently, Zhang et al reported that the heterogeneous coating interface of MXene and porous graphene can considerably ameliroate the rate performance and prolong the cycling ability of SiO. 23 However, the graphene outer layer will intensify the deoxidation process of solvent molecules, forming an unstable solid electrolyte interface (SEI).…”
Section: Introductionmentioning
confidence: 99%